Method of dynamic redistribution of the productivity package of switchboard between its ports with the use of mechanism of prognostication of pulsations of traffic - Муранов, О. С.; Чуприн, В. М.; Потапов, В. Г. (Problems of Informatization and Control, 2008)
Proposed method of data streams dynamic redistribution among devices ports of packets commutation, that allows increasing maximum network equipment load without deterioration of given network services quality. The method is based on spline-interpolation in the real time of traffic ripple dynamic characteristics on switch’s ports and on adaptive auto-adjustment of switch’s ports bandwidth depending on characteristics of traffic ripple. To reduce the volume of processed data during interpolation it is suggested to use the known methods of experimental data generation. Examples of switch’s ports bandwidth auto-adjustment rules are given, that implement the considered method